The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4103/1735-5362.189314
|View full text |Cite
|
Sign up to set email alerts
|

Antileishmanial activity of prenylated coumarins isolated from Ferulago angulata and Prangos asperula

Abstract: Leishmaniasis has a wide spectrum of signs and symptoms due to infection to numbers of Leishmania species and makes enormous mortality and morbidity. There are clues of antileishmanial effects of prenylated coumarins. Apiaceae family is one of the most important sources of coumarins. Air-dried aerial parts of Ferulago angulata and fruits of Prangos asperula were extracted with n-hexane, using a soxhlet apparatus. The solvents were evaporated under reduced pressure. Column chromatography and crystallization pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Monitoring of the column chromatography was carried out by thin layer chromatography (Pre-coated silica gel GF 254 plates, Merck) and fractions giving similar spots under UV (254 and 366 nm) were combined. The structures of the compounds were elucidated by 1 H-NMR and 13 C-NMR (Bruker Avance 400 DRX, 400 MHz for 1 H and 100 MHz for 13 C) spectral analysis, as well as by comparing with the data published in the literature.…”
Section: Isolation and Purification Of The Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Monitoring of the column chromatography was carried out by thin layer chromatography (Pre-coated silica gel GF 254 plates, Merck) and fractions giving similar spots under UV (254 and 366 nm) were combined. The structures of the compounds were elucidated by 1 H-NMR and 13 C-NMR (Bruker Avance 400 DRX, 400 MHz for 1 H and 100 MHz for 13 C) spectral analysis, as well as by comparing with the data published in the literature.…”
Section: Isolation and Purification Of The Compoundsmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] In 2006, Sajjadi et al reported the isolation of two prenylated coumarins, suberosin and suberosin epoxide, from aerial parts of this plant. 13 In their further studies, suberosin epoxide has been demonstrated to possess considerable antiprotozoal activity against Leishmania major and Plasmodium berghei. 13,14 Xanthotoxin, isoimperatorin, oxypeucedanin, oxypeucedanin hydrate, prantschimgin, quercetin, rutin, along with stigmasterol, β-sitosterol and β-sitosterol linoleate are the other compounds reported from the aerial parts of F. angulata during previous phytochemical studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leishmaniasis is caused by protozoan parasites of the genus Leishmania and transferred into the host by the bite of infected female phlebotomine sandflies. Based on WHO reports, the pathogen is endemic over 90 countries ( 1 ) and Iran is one of the endemic areas of this pathogen ( 2 3 ). Leishmaniasis is estimated to involve about 2 million new cases per year ( 4 ) and despite such prevalence, leishmaniasis is categorized as a neglected tropical disease due to its strong relationship with poverty and also considering the limited resources invested in its diagnosis, treatment, and control ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Coumarins have various biological properties related to their chemical structure [ 25 , 26 , 27 ]. Some coumarins have vasorelaxant activity in coronary vessels and some other showed hypotensive [ 22 ], antiviral [ 28 ], antileishmanial [ 29 ] anti-inflammatory [ 30 ] and antispasmodic [ 31 ] effects. Furanocoumarins are also widely used in the treatment of leucoderma and psoriasis due to their photosensitivity properties [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%